Monetary Policy in a Small Open Economy with Credit Goods Production - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 1998)
The paper analyzes the effects of monetary policy in a dynamic model of a small open economy with cash and credit goods production, where government consumption is financed by seignorage. It shows that the interrelationships between the growth rate of the monetary aggregate and the technological properties of the economy have an important bearing on the existence and uniqueness of equilibrium, the optimal inflation rate, and the occurrence of explosive hyperinflations. In consequence, the paper concludes that monetary policy does matter in the long run.